Circus Philosophicus - Maxwell Kennel (Speculations 3, 2012)
After four vivid pages spent describing “the myth of the ferris wheel” Graham Harman sets into what some have called the most accessible introduction to Object Oriented Ontology to date. At around 25,000 words in length Circus Philosophicus reads nicely in one extended sitting, and very readily yields rewards to both the specialist and non-specialist reader. Situated within Harman’s expand-ing oeuvre Circus Philosophicus is not readily comparable with any of his other work work, with the possible exception of the forthcoming Treatise on Objects (Open Humanities Press), which Harman describes as having a similar sort of prose. 1The incomparable genre of Circus Philosophicus seems to have been the goal from the beginning, a fact made evident by the rear cover blurb which describes the goal to “restore myth to its central place in the discipline.” The following review will give a brief summary of the first half of Circus Philosophicus highlighting some pertinent details, while of-fering some closing comments on the interesting placement of the work within both the genre and the discourse of Object Oriented Ontology.